A Psychometric Examination of the Abbreviated Version of the Parenting Styles Scale Using a Sample of Chilean Adolescents - José Luis Gálvez-Nieto; Karina Polanco-Levicán; Sonia Salvo-Garrido; María Pía Godoy-Bello (MDPI AG, 2024)
Parenting styles have been related to a series of variables that contribute positively to adulthood. The maternal and paternal parenting styles scale is a measure that presents a multidimensional structure of six correlated factors. However, the version available for Chile is extensive, with 82 items measuring this latent trait. Therefore, the aim of this study was to examine the psychometric properties of the reliability and validity of the abbreviated version of the maternal and paternal parenting styles scale using a sample of Chilean adolescents. The sample consisted of 2131 students of both the male and female sexes (51% males and 49% females) with a mean age of 15.85 years (SD = 1.37). The results of the exploratory and confirmatory factor analyses supported the six-factor correlated model, showing robust psychometric indices for both modelling approaches. In relation to the factorial invariance models, the results show factorial equivalence at the scalar invariance level for the variables of sex, age, academic achievement, and type of school. The scale showed adequate levels of reliability. This study concludes that the abbreviated version of the maternal and paternal parenting styles scale is a reliable and valid instrument for its application in Chilean adolescents.